NEGOTIATION OF MEANING IN SPEAKING CLASS: A CASE STUDY - Dentamira Rafi Kumala Sari; Rahman Hakim; Akhmad Baihaqi (Cakrawala Pedagogik, 2026)
The purpose of this study was to investigate the components, types, and role of negotiation of meaning among students during oral interaction in a speaking class of eleventh grade at one private vocational school in Tangerang, Indonesia. The researchers employed a case study including non-participant observation, unstructured interviews, and documentation as data collection techniques. The participants of this study were thirty pharmacy students. The data analysis processes were reducing the data, data display, and drawing/ verification. The procedures of this research included: collecting the data, observing students conversations, analyzing the data, and concluding/interpreting the data. The findings revealed that the most frequently used component was trigger, and the most commonly used type was repetition. The role of negotiation of meaning facilitated collaborative efforts among students to seek clarification, creating a supportive environment. This process boosted confidence, aided comprehension, and encouraged active contributions to language development, fostering a mutually beneficial learning community.